2016
DOI: 10.3151/jact.14.691
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale Review for Possible Mechanisms of Natural Frequency Change of Reinforced Concrete Structures under an Ordinary Drying Condition

Abstract: Based on a review from a view point of multi-scale perspective, it is concluded that possible mechanisms of natural frequency change of concrete structures under an ordinary drying condition are reduction of Young's modulus of concrete and stiffness reduction of reinforced concrete member due to shrinkage-induced cracking. Both two mechanisms can be provoked by drying, which is natural environmental condition for all the building structures. This natural frequency change is important for the integrity analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…Previous studies found that the shrinkage strain of matured cement paste was a function of the incremental statistical thickness of ad- sorbed water films (Badmann et al 1981), as shown in Fig. 120 (Maruyama 2016). Above 40% RH, the shrinkage associated with the first desorption process has a linear relationship with the incremental statistical thickness of adsorption.…”
Section: Computational Cement-based Materials Model (Ccbm)mentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies found that the shrinkage strain of matured cement paste was a function of the incremental statistical thickness of ad- sorbed water films (Badmann et al 1981), as shown in Fig. 120 (Maruyama 2016). Above 40% RH, the shrinkage associated with the first desorption process has a linear relationship with the incremental statistical thickness of adsorption.…”
Section: Computational Cement-based Materials Model (Ccbm)mentioning
confidence: 74%
“…Specimens exhibited slight shrinkage, as shown by the length changes in Fig. 40 (a); this was in the range of normal drying shrinkage (Maruyama 2016). pressive strength data.…”
Section: Ht: Concretementioning
confidence: 79%
See 2 more Smart Citations
“…Parrot (1992) and Dias (2004) indicated that the sorptivity corresponds to the amount of water lost by drying. C-S-H is known to shrink due to drying (Maruyama 2016) and Taylor et al (1999) mentioned that dried C-S-H swelled due to absorbed water. The absorption of water into concrete was reduced compared to that of n-decane and this difference was explained by the swelling of C-S-H.…”
Section: Introductionmentioning
confidence: 99%